Innovative work behavior and job stress: Does supervisory support matter? - Yulabi, Ruchan; Park, Hun Myoung (Faculty of Psychology, Universitas Diponegoro, 2024)
Background: Studies found both positive and negative outcome of innovative behavior. Previous research has explored the intended outcomes of innovative work behavior (IWB) extensively. However, there are limited studies examining the unintended impacts of innovative behavior. Therefore, study on this gap of knowledge is still worth exploring. Purpose: This paper study aims to test the negative impacts of innovative work behavior (IWB) on job stress. While previous studies stressed identifying factors promoting innovative work behavior, this study tries to uncover the negative impact of innovative work behavior along with how to buffer it. Method: 339 officers working in a public sector organization were asked to fill out questionnaires. Of 142 returned questionnaires, 118 were valid. The ordinary least square (OLS) regression was used to test the developed hypotheses.Findings: This study found that IWB positively correlated with job stress (r = .36, p < .01). Moreover, results indicated that PSS negatively moderated the relationship between IWB and job stress, b = -1.49, t(118) = -3.22, p < .01.Implication: Leaders in the public sector organization should be aware that while IWB is generally beneficial, it may cause the side effect of job stress for the innovator. Therefore, support from the supervisor is essential to buffer job stress.